ANALYSIS TURN-TAKING USED BY PRINCESS POPPY AND BRANCH IN THE TROLLS MOVIE - Karmila, Iis; Lisdawati, Ida (PROJECT (Professional Journal of English Education), 2020)
This research about spoken language which is discussed in discourse analysis. In this research, researcher only focused on turn-taking, especially in the overlap and interruption section. Reseacher used quantitative methods and Guttman scale in processing data obtained from conversation in a movie called Trolls. Researcher choose a movie because in general a movie always contains conversations as well as in that movie. In the movie, researcher only analyzed 2 characters, Princess Poppy and Branch. The purpose of this research was to determine how much turn-taking was used by Princess Poppy and Branch. The results of the analysis showed that the turn-taking by Princess Poppy was 157 while the Branch was 110. The researcher used a table to show the results based on the theory of turn-taking. We can see in table 1 and table 2 that the amount of overlap is more dominant than interruption. The result of the analysis showed frequency overlap Princess Poppy is 82% of the total 128 and interruption frequncy is 18% of the total 29 times. While in tabel 2 it shows that the number of overlap conducted by Branch was 81 with a frequency of 74% and 29 interruption with a frequency of 26%. Keywords:  Discourse Analysis, Interruption, Overlap, Spoken Language, Turn-taking